The official Veganuary cookbook : 100 amazing vegan recipes for everyone! (Harper Thorsons, 2023)
Love food? Want to try new recipes? Curious about plant-based cooking? Delicious food is at the heart of the Veganuary ethos so, whether you're vegan, veggie, flexi, or simply want to try a few more veg-centric recipes, we've included something for absolutely everyone in this book. From one-pots and traybakes to sweet and savoury breakfasts, creamy pastas, crunchy burgers, fresh and seasonal salads, warming pies and mouth-watering desserts - you won't know which to pick first! We've included a handy list of store-cupboard essentials and zero-waste inspiration to make your mealtimes as efficient, eco-friendly and economical as possible. So, open up for food that's vibrant, colourful, packed with flavour and full of life!"--Back cover.